Case ReportExtensive leg and foot ulcers as a manifestation of cryoglobulinaemia with accompanying monoclonal gammopathy of undetermined significance - Krasowska, Dorota; Kozłowicz, Katarzyna; Legieć, Wojciech; Nowicka, Patrycja; Dobel, Martyna; Krzowska-Firych, Joanna; Pietrzak, Aldona; Dmoszyńska, Anna; Chodorowska, Grażyna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2011)
Cryoglobulinaemia is characterized by the presence of cryoglobulins in serum, which precipitate at temperatures below 37 ° C and dissolve on warming. Cryoglobulins may form immune complexes or circulating aggregates, which induces clinical symptoms of leucoclastic vasculitis or leads to hyperviscosity syndrome. Clinical manifestations have various locations; lesions mostly appear on the skin, but may also involve many different organs. Clinically, cryoglobulinaemia is classified into idiopathic cryoglobulinaemia without any accompanying disease and secondary cryoglobulinaemia, which occurs in association with other diseases, e.g. infectious, lymphoproliferative and connective tissue diseases. Treatment of cryoglobulinaemia depends on a concomitant disease. The aim of the present study was to describe a case of extensive leg and foot ulcers as a manifestation of cryoglobulinaemia accompanying monoclonal gammopathy of undetermined significance. Key words: ulcers, cryoglobulins, monoclonal gammopathy.